Nexus of Sustainable Social Supply Chain Practices, Local Supplier Development and Safety Performance - Halili, Munira; Fernando, Yudi; Tseng, Ming-Lang (Asia Pacific Industrial Engineering & Management Systems, 2021)
he purpose of this study is to develop a theoretical model that examines the effect of sustainable social supply chain practices on safety. The development of local suppliers has been identified as a mediating variable as a way to improve company’s social performance. This study focused on manufacturing companies registered with the Malaysian Federation of Manufacturers. The 144 questionnaires data were analyzed using structural equation modelling. The findings show that sustainable practices have a significant impact on local supplier development. Furthermore, local supplier development mediated the relationship between sustainable social supply chain practices and safety. It also increases awareness of sustainable practices that can have a substantial impact on firms' attempts to implement safety measure, allowing decision-makers and industrial managers to examine the extent of positive influences on increasing companies’ safety measure.